Prospects of Hyperloop Transportation Technology: A Case of China - Md. Abdur Rob; A S M Sharifuzzaman Sagar; Md. Nasir Uddin (International Journal of Engineering and Management Research, 2019)
Hyperloop transportation technology is amongst the most promising sustainable and climate-friendly transportation systems of the modern era. Now China has taken steps to build this transportation system in Tongren city, which located on Guizhou's eastern part [8]. So far, not much work has been conducted on the prospects of this technology, especially for China. In this paper based on extensive literature review, we have analyzed the prospects of this technology in China. Furthermore, this article also discusses the possible hurdles and proposes some suggestions for overcoming the problems in the adoption of this climate-friendly technology.